2019
DOI: 10.1108/bij-06-2018-0162
|View full text |Cite
|
Sign up to set email alerts
|

A neural network approach for retailer risk assessment in the aftermarket industry

Abstract: Purpose Given the competitive environment and complicated relationships in supply chains in the modern era, it is important to take into account internal and external risks. In addition, proper methods must be designed to evaluate these risks correctly. The purpose of this paper is to provide a suitable map based on the artificial neural network technique to assess and classify the risk levels of retailers who have interconnected rules in the downstream of the supply chain. Design/methodology/approach In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 68 publications
0
13
0
2
Order By: Relevance
“…Perceived online service quality: This variable is a function of the direction and magnitude of the comparisons between the expected and perceived services. The perceived online service quality reflects the extent to which a website can manage to facilitate shopping and efficient delivery of products to customers (Rezaei, Shokouhyar and Zandieh, 2019) developed 11 factors of e-services quality (E-SERVQUAL) and considered the website aesthetics as one of the dimensions measuring the quality of online services. To detect the e-service quality dimensions, Rowley (2006) reviewed 29 studies from 1996 to 2006 and concluded that the aesthetics along with components such as ease of use, ease of navigation, design and ease of ordering, has been considered in 25 resources as a factor affecting the perceived online service quality.…”
Section: Effects Of Visual Aesthetic Of Web Pagesmentioning
confidence: 99%
“…Perceived online service quality: This variable is a function of the direction and magnitude of the comparisons between the expected and perceived services. The perceived online service quality reflects the extent to which a website can manage to facilitate shopping and efficient delivery of products to customers (Rezaei, Shokouhyar and Zandieh, 2019) developed 11 factors of e-services quality (E-SERVQUAL) and considered the website aesthetics as one of the dimensions measuring the quality of online services. To detect the e-service quality dimensions, Rowley (2006) reviewed 29 studies from 1996 to 2006 and concluded that the aesthetics along with components such as ease of use, ease of navigation, design and ease of ordering, has been considered in 25 resources as a factor affecting the perceived online service quality.…”
Section: Effects Of Visual Aesthetic Of Web Pagesmentioning
confidence: 99%
“…Discussing the challenges of universities, especially in the field of telecommunication and information systems, this study had concluded that sustainability was an important challenge for universities, governments and companies, and there were alternative ways of resolving sustainability, currently being addressed by the Intergovernmental Panel on Climate Change (IPCC). However, the potential impact of IT on the best design of transportation, logistics, office and home systems; and for the most part, the fact that one of the problems of design stability was sustainability had been ignored (Rezaei et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because the use of the correct data set becomes important at this stage. The correct structure established will enable the production of more realistic predictions [18].…”
Section: Artificial Neural Networkmentioning
confidence: 99%